2016
DOI: 10.1089/ten.tea.2015.0203
|View full text |Cite
|
Sign up to set email alerts
|

Superior Tissue Evolution in Slow-Degrading Scaffolds for Valvular Tissue Engineering

Abstract: Synthetic polymers are widely used to fabricate porous scaffolds for the regeneration of cardiovascular tissues. To ensure mechanical integrity, a balance between the rate of scaffold absorption and tissue formation is of high importance. A higher rate of tissue formation is expected in fast-degrading materials than in slow-degrading materials. This could be a result of synthetic cells, which aim to compensate for the fast loss of mechanical integrity of the scaffold by deposition of collagen fibers. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…However, due to their stiffness, they were not considered completely suitable for a heart valve scaffold, and several other alternatives have been tested ever since to overcome this limitation, including PCL . Also, a recent publication by Brugmans et al indicated that slow‐degrading scaffolds (such as those made of PCL) show a superior tissue evolution when compared to fast‐degrading materials (like PGA), keeping their structural integrity and shape over time .…”
Section: Resultsmentioning
confidence: 99%
“…However, due to their stiffness, they were not considered completely suitable for a heart valve scaffold, and several other alternatives have been tested ever since to overcome this limitation, including PCL . Also, a recent publication by Brugmans et al indicated that slow‐degrading scaffolds (such as those made of PCL) show a superior tissue evolution when compared to fast‐degrading materials (like PGA), keeping their structural integrity and shape over time .…”
Section: Resultsmentioning
confidence: 99%
“…Poly-ε-caprolactone is one of the favored synthetic biomaterials as it combines many desirable properties such as biocompatibility, biodegradability, mechanical strength and flexibility [ 17 ]. Its biocompatibility and strength with good results in cell infiltration [ 19 , 32 ] makes it particularly interesting for the production of implantable long-term prostheses. PCL has already been approved by the Food and Drug Administration (FDA) for specific uses in the human body [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reimer et al 46 performed fatigue testing under pulsatile conditions on decellularized tissue valves obtained from ovine dermal fibroblasts, but did not specifically evaluate scaffold degradation nor were the effects of enzymes considered. Sant et al 57 as well as Brugmans et al 58 evaluated in a pulse duplicator the degradation of heart valve leaflet made of fastdegrading polyglycolic acid scaffolds coated with poly-4hydroxybutyrate and slow-degrading poly-ε-caprolactone. Yet, the evaluation was not based on a fully assembled valve.…”
Section: Discussionmentioning
confidence: 99%